Are we wasting our children's time by giving them more homework? - Ozkan Eren; Daniel J. Henderson (Institute for the Study of Labor (IZA), 2011)
Following an identification strategy that allows us to largely eliminate unobserved student and teacher traits, we examine the effect of homework on math, science, English and history test scores for eighth grade students in the United States. Noting that failure to control for these effects yields selection biases on the estimated effect of homework, we find that math homework has a large and statistically meaningful effect on math test scores throughout our sample. However, additional homework in science, English and history are shown to have little to no impact on their respective test scores.
urn:nbn:de:101:1-201104133689
Keywords: C23; I21; I28; 330; first differencing; homework; instrumental variable; selection bias; unobserved traits; Allgemeinbildende Schule; Heimarbeit; Bildungsniveau; Schätzung; USA